Biosynthesis of a biopolymer poly(3-hydroxybutyrate) from a mixture of palm oil and 2-butanol as carbon sources - Djamaan, Akmal (INDONESIAN JOURNAL OF PHARMACY, 2011)
Polyhydroxybutyrate  [P(3HB)]  are  synthesized  as  carbon  and  energy reserve materials by many types of microorganisms under certain environmental condition. These biosynthetic polyesters have much received attention as they can  be  considered  to  be  a  source  for  developing  novel  biodegradable  plastic materials for pharmaceutical, medical and biodegradable packages industries. In this case,  Erwiniasp. USMI-20, a locally soil isolated microorganism has been found  to accumulate  P(3HB)  in its  cells  during  growth  on  mineral-media  with  a mixture of palm oil and 2-butanol as carbon source. Fermentation process was conducted  through  a  feedbatch  cultivation  under  aerobic  condition  at  pH  7.0, incubation temperature 30 oC, and agitation rate of 200 rpm for 48 hours. The characterization of the  polymer production  was based  on  cell growth  (biomass) and  polymer  content  detected  by  a  gas  chromatography  methode.  Result showed  that  from  a  mixture  of palm  oil:2-butanol  (4.62g/L+0.89g/L) produced P(3HB) of 50.86 %w/w with biomass of 5.82g/L; a mixture of palm oil:2-butanol (4.62g/L+1.65g/L) produced  P(3HB)  of 57,77%  w/w  with  biomas  of 6.01g/L,  a mixture  of  palm  oil:2-butanol  (4.62g/L+2.48g/L)  produced  P(3HB)  of  55.85%w/w with  biomass  of  6.57g/L,   a  mixture  of palm  oil:2-butanol (4.62g/L+3.29 g/L) produced P(3HB) of 56.37% w/w with biomass of 6.67g/L and a mixture of palm  oil:2-butanol  (4.62g/L+4.12g/L)  produced  P(3HB)  of  47.70%  w/w  with biomass of 6.33g/LKey words:biopolymer, poly(3-hydroxybutyrate), palm oil, and n-butanol.